NEUROPROTECTIVE TREATMENT OF GLAUCOMA - Walewska, Zuzanna; Dejewska, Natalia; Gadomska, Urszula; Maksymiuk, Jowita Wiktoria; Onopiuk, Mateusz; Daniluk, Mikołaj; Szumska, Zuzanna (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Glaucoma is a progressive optic neuropathy and a leading cause of irreversible blindness, characterized by degeneration of retinal ganglion cells and structural damage to the optic nerve. Although reduction of intraocular pressure remains the primary treatment, disease progression often continues due to additional neurodegenerative mechanisms. This review summarizes current evidence on neuroprotective strategies in glaucoma.Methods: The narrative review with a structured search strategy was conducted to evaluate current evidence on neuroprotective treatment in glaucoma using the PubMed database. Eligible studies included original research articles, published between January 2016 and March 2026. The study selection process was conducted in accordance with PRISMA guidelines. Of 79 identified records, 18 studies met inclusion criteria and were qualitatively synthesized with emphasis on clinical applicability.Results: Neuroprotective therapies in glaucoma show heterogeneous outcomes across functional, structural, and electrophysiological measures. Citicoline and nicotinamide demonstrate the most consistent benefits, while memantine and Ginkgo biloba have not shown significant efficacy in clinical trials; other interventions exhibit modest or variable effects.Conclusion: At present, lowering intraocular pressure remains the only proven strategy to slow glaucoma progression. Neuroprotection should be considered an adjunctive, investigational approach.